How Islamic Psychospiritual Contribute to Balanced Mental Health and Human Wellbeing - Othman, Khatijah; Yaakub, Muhamadul Bakir; Kamal, Nur Fatinni Mohamad; Shafie, Amin Al Haadi (Journal of Posthumanism, 2025)
Psychospirituality is the integration of two entities, namely psychology and spirituality. Islamic psychospirituality encompasses the Islamic approach to psychological and spiritual knowledge. Therefore, Islamic psychospiritual treatment explains how Islamic spirituality plays its role as a contributing factor in treating human stability in mental health and well-being. Most importantly, when humans want to function as leaders on this earth, they should have a stable and balanced mind through their actions and the way they communicate with other people and the environment. However, the problem occurs if mental health is in doubt, unstable or fragile every time they face life’s challenges. Here, the role of Islamic psychospiritual treatment on mental health appears critical since it builds relationships and brings inner spiritual and intellectual direction that is integrated with faith/belief in the Creator/God. This situation leads to stability of mind, body and soul which contributes to human well-being. Well-being of life is a state that humans seek to ensure that a person feels good and functions well. Having positive emotions such as joy and satisfaction as well as the ability to develop life’s potential is something that is needed. Reshaping the determinants of mental health often requires action from external factors and from the health sector. Whereas, WHO conventionally addresses well-being issues through program promotion and prevention involving the education, labor, justice, transportation, environment, housing, and welfare sectors. On the other hand, Islam emphasizes the aspect of psychospiritual strengthening to balance mental health and well-being. Therefore, this conceptual study harnesses that there is a fundamental relationship on how Islamic psychospiritual treatment affects to balance mental health and overall human well-being.